A Case of Pneumothorax after Treatment with Lenvatinib for Anaplastic Thyroid Cancer with Lung Metastasis. (28th March 2018) - Yamazaki, Haruhiko; Iwasaki, Hiroyuki; Yamashita, Toshinari; Yoshida, Tatsuya; Suganuma, Nobuyasu; Yamanaka, Takashi; Masudo, Katsuhiko; Nakayama, Hirotaka; Kohagura, Kaori; Rino, Yasushi; Masuda, Munetaka
Abstract : A 63-year-old man was diagnosed with multiple lung metastases from anaplastic thyroid cancer and received lenvatinib. Follow-up computed tomography on day 34 of lenvatinib treatment showed pneumothorax. The pneumothorax was temporarily improved with chest drainage. However, pleurodesis was performed to treat a relapse of the pneumothorax. Pneumothorax during chemotherapy for a malignant tumor is considered a relatively rare complication. This case is the first documentation that pneumothorax may develop during lenvatinib treatment. The possible development of pneumothorax should be considered when lenvatinib is used in patients with lung metastasis.